Paradigmatic Shifts in Corpus-Driven Contrastive Linguistics and Translation Studies: Navigating Complexities of Multilingual Discourse - Kamolov Dilshod Khusniddinovich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This study explores language comparison methods and their relationship with translation research. It focuses on the theoretical foundations of contrastive linguistics, the methodologies used to compare languages at various linguistic levels, and the implications of such comparisons for translation practices. By integrating linguistic analysis and translation studies, the paper highlights how structural, semantic, and cultural differences between languages influence translation strategies. The research contributes to the growing field of applied linguistics by showing that translation is both a linguistic and cultural process.